Portrait of Junior High School Students’ Motivation in Learning Geometry - Cahyadi, Muhammad Rizki; In'am, Akhsanul; Rizki, Nopia; Laila, Alfi Rachma Nisfi (Universitas Suryakancana, 2023)
Geometry is a branch of mathematics that deals with shapes and dimensions. In learning geometry it is not uncommon for students to experience difficulties and mistakes in understanding concepts. Motivation is an important factor that needs to be considered so that students remain enthusiastic in the learning process of geometry. Motivation becomes a driving force and trigger for students to be active in the learning process. This research aims to provide a portrait of the motivational condition of junior high school students in learning geometry. This research is quantitative descriptive. The research was conducted on 136 junior high school students who were randomly selected from 3 different cities, namely Medan, Tulungagung and Lombok. The data collection technique was carried out using a motivational questionnaire instrument. Data analysis was performed with descriptive statistical analysis. The results of this research indicate that junior high school students' motivation in learning geometry is high with a score of 3.96 on a scale of 1-5.